Analisis Kapasitas Efektif Tampungan Kali Pancir - Winda Harsanti; Moh. Zenurianto; Marjono; Sitti Safiatus Riskijah; Ninda Prabawanti (Jurnal Teknik Ilmu dan Aplikasi, 2024)
Kali Pancir is one of the rivers in Jombang Regency which often experiences flooding. The cause was heavy rain and the critical condition of the embankments. In this research, flood discharge analysis was carried out using synthetic hydrographs and hydraulic modeling for river flow. The data needed is rain data from rain stations around the Pancir River and river profiles. The method used to calculate flood discharge is the Nakayasu Synthetic Unit Hydrograph for 6 different return periods. Simulation using HEC-RAS software is used to simulate flow profiles to determine river cross-sections that are critical to flooding. Based on the results of the calculation analysis, it was found that the peak flood discharge occurred at 3.5 hours. The greater the return period, the greater the river cross section that experiences overflow. At a return period of 1.01 years, the critical cross section starts at STA 45, while at a return period of 50 years, the critical cross section occurs starting at STA 6.